ANALISIS SPASIAL DAERAH POTENSI RAWAN LONGSOR DI KOTA AMBON DENGAN MENGGUNAKAN METODE SMORPH - Heinrich Rakuasa; S Supriatna; Mangapul Parlindungan Tambunan; Melianus Salakory; Wiclif. S. Pinoa (Jurnal Tanah dan Sumberdaya Lahan, 2022)
The geographical condition of Ambon City, which is 75% a hilly area resulted in most communities building in marbled areas with slopes above 20%, which has the potential to threaten life and landslide disasters. This study simply looked at the influence of slopes and slope shapes in Ambon City that can be analyzed using geographic information systems (GIS) to map areas that have the potential for landslides. Identification and mapping of potential landslide areas have an important role as an effort in overcoming and anticipating the occurrence of landslide disasters. This study aimed to analyze the spread of potential landslide areas in Ambon City based on the results of SMORPH modeling. The study used the slope morphology or SMORPH method, which has a better degree of accuracy than the Storie Index and SINMAP methods to identify and classify potential landslide areas based on the matrix between slope shape and slope angle. This study resulted in 4 levels of landslide potential areas, namely very low, low, medium and high potential. Areas with high landslide potential dominate the northern and southern parts of Ambon City. In the region, most landslides occur in the form of sunken and convex slopes. The region has a hilly and mountainous topography with a steep slope. The results of this research using the SMORPH method can illustrate that the slope of the increasingly higher slope accompanied by the shape of a convex or concave slope will cause the potential for landslides that are higher in the region.